2007
DOI: 10.1002/uog.3930
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic growth factor levels in maternal and fetal blood: correlation with Doppler ultrasound parameters in pregnancies complicated by pre‐eclampsia and intrauterine growth restriction

Abstract: Objectives To correlate levels of angiogenic growth factors with Doppler ultrasound parameters in pregnancies complicated by pre-eclampsia and intrauterine growth restriction (IUGR). Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
63
1
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 34 publications
9
63
1
8
Order By: Relevance
“…50 In this study, cord plasma PlGF levels were below the detection limit in both groups, and similar findings were previously reported. 51,15 In our study, sFlt-1 levels in cord plasma were increased, although they were not significant in preeclampsia, consistent with earlier reports. 51 Some studies have also shown that infants with maternal preeclampsia had higher cord blood sFlt-1 but lower PlGF and VEGF levels.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…50 In this study, cord plasma PlGF levels were below the detection limit in both groups, and similar findings were previously reported. 51,15 In our study, sFlt-1 levels in cord plasma were increased, although they were not significant in preeclampsia, consistent with earlier reports. 51 Some studies have also shown that infants with maternal preeclampsia had higher cord blood sFlt-1 but lower PlGF and VEGF levels.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies carried out in Western countries have consistently reported increased levels of plasma sFlt-1 8,15,[34][35][36][37][38][39][40][41] in mothers with preeclampsia compared with normotensive women. Our results suggest that Indian women with preeclampsia also have a similar increase in plasma sFlt-1 levels.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…One of the main features in the placenta from a preeclamptic pregnancy is failure of spiral artery remodeling, a phenomenon linked not only with reduced maternal blood flow toward the placenta [4] but also with high velocity and pressure of maternal inflow that may impair the placental villous structure [5]. Both a reduction in placental blood flow and impaired placental structure have been associated with neonatal complications following preeclampsia, such as growth retardation [4][5][6][7]. Specifically, Doppler studies reveal that impaired feto-placental blood flow is mainly evident in women with early-onset preeclampsia (EOPE) [8] rather than late-onset preeclampsia (LOPE) [9].…”
Section: Introductionmentioning
confidence: 99%